Effects of domperidone and medroxyprogesterone acetate on ventilation in man - Javaheri, Shahrokh; Guerra, Luis F. (Respiration physiology, 1990)
If endogenous dopamine acts as an inhibitory neurotransmitter in the carotid bodies in man, domperidone (DP), a selective dopamine D-2 receptor antagonist should stimulate carotid bodies and augment ventilation. Furthermore, the combination of a central ventilatory stimulant, medroxyprogesterone acetate (MPA), with a peripheral ventilatory stimulant, DP, may produce an additive/synergistic ventilatory effect. We conducted a double-blind, placebo-controlled (P), cross-over trial comparing MPA 20 mg three times daily (TID) and DP (20 mg TID) alone and together in 8 healthy male human subjects. Drug effects were measured after 7 days, and a two-week drug washout period was allowed. MPA significantly increased alveolar ventilation (V̇ a), and slopes of hypercapnic and hypoxic ventilatory responses. Domperidone alone significantly increased the slope of the hypoxic response; however, V̇ a and Pa CO 2 did not change significantly. The combination of MPA and DP resulted in ventilatory changes similar to MPA alone. We conclude that in man endogenous dopamine acts as a modulator of chemoreception during hypoxemia, but plays no major role tonically in control of ventilation during normoxemia and normocapnia. Lack of additive effect with combined DP and MPA suggests that these drugs may share the same final common pathway in the process of chemoreception.